1990
DOI: 10.1038/343562a0
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the malignant hyperthermia susceptibility locus to human chromosome 19ql2–13.2

Abstract: Malignant hyperthermia (MH) is an inherited human skeletal muscle disorder and is one of the main causes of death due to anaesthesia. The reported incidence of MH varies from 1 in 12,000 in children to 1 in 40,000 in adults. MH is triggered in susceptible people by all commonly used inhalational anaesthetics; it is characterized by a profoundly accelerated muscle metabolism, contractures, hyperthermia and tachycardia. Susceptibility to MH (MHS) is predicted by contracture tests on muscle tissue obtained by bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
107
0
9

Year Published

1998
1998
2005
2005

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 360 publications
(120 citation statements)
references
References 22 publications
3
107
0
9
Order By: Relevance
“…Linkage between inheritance of MH and RYR1 markers or chromosome 19q markers, identified RYR1 as a candidate gene for MH in humans [36,37]. The discovery of several RYR1 mutations that could be linked to MH established RYR1 as a causal gene for MH.…”
Section: T H E M O L E C U L a R B A S I S F O R M A L I G N A N T H mentioning
confidence: 99%
“…Linkage between inheritance of MH and RYR1 markers or chromosome 19q markers, identified RYR1 as a candidate gene for MH in humans [36,37]. The discovery of several RYR1 mutations that could be linked to MH established RYR1 as a causal gene for MH.…”
Section: T H E M O L E C U L a R B A S I S F O R M A L I G N A N T H mentioning
confidence: 99%
“…The latter observation has led to the suggestion that MH, heat stroke, and exercise-induced rhabdomyolysis might have a common denominator (2,6,7). The underlying causes of MH are abnormalities in the skeletal muscle calcium metabolism (8,9) and molecular genetic studies have mapped the primary locus of MH to chromosome 19q, the gene encoding the ryanodine receptor calcium release channel (RYR1) (2,4,10). Approximately 50% of MH families have mutations in the RYR1 gene, and mutations have been reported in other loci (for recent reviews, see Refs.…”
Section: Malignant Hyperthermia (Mh)mentioning
confidence: 99%
“…Since MH is inherited as an autosomal dominant trait, causal mutations in the RyR1 gene (RYR1) have been investigated. Thus, MacLennan et al (10) and McCarthy et al (11) showed in their linkage study that the MH phenotype segregates with markers for RYR1 in the locus q13.1 of human chromosome 19. To date, twenty-six missense mutations (1 -3, 12 -16) in the cDNA of RyR1 have been identified among individuals having MH and /or the associated central core disease (CCD).…”
mentioning
confidence: 99%